2016
DOI: 10.1021/acs.est.6b01072
|View full text |Cite
|
Sign up to set email alerts
|

A Multimethod Approach for Investigating Algal Toxicity of Platinum Nanoparticles

Abstract: The ecotoxicity of platinum nanoparticles (PtNPs) widely used in for example automotive catalytic converters, is largely unknown. This study employs various characterization techniques and toxicity end points to investigate PtNP toxicity toward the green microalgae Pseudokirchneriella subcapitata and Chlamydomonas reinhardtii. Growth rate inhibition occurred in standard ISO tests (EC values of 15-200 mg Pt/L), but also in a double-vial setup, separating cells from PtNPs, thus demonstrating shading as an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 42 publications
3
37
0
5
Order By: Relevance
“…In this study, NPs were adsorbed to algal cells, as frequently observed in other studies (Hartmann et al 2013;Nolte et al 2017;Sørensen et al 2016). It can be expected that NPs excessively covering algal cells are more likely ingested by filter feeding organisms since the mesh of the filtering apparatus is developed to concentrate particle in the mm-range such as algal cells.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, NPs were adsorbed to algal cells, as frequently observed in other studies (Hartmann et al 2013;Nolte et al 2017;Sørensen et al 2016). It can be expected that NPs excessively covering algal cells are more likely ingested by filter feeding organisms since the mesh of the filtering apparatus is developed to concentrate particle in the mm-range such as algal cells.…”
Section: Discussionsupporting
confidence: 70%
“…However, although such tests are useful for investigating shading caused by dispersion turbidity they will not detect localized shading on a cellular level caused by the encapsulation of the cells by ENPs, which can, therefore, not be excluded 54. Significant shading was identified for platinum ENPs of relatively low toxicity with an EC 50  value at the higher end of the classification range of 10–100 mg L −1 26. This exemplifies the need to account for shading effects when testing for hazard identification purposes.…”
Section: Physical Effects Of Enps In Aquatic Toxicity Testsmentioning
confidence: 99%
“…Hence, valence state and bioavailability of redox-active ions are strongly related to the generation of ROS. Numerous inorganic ENMs, such as Ag, Pt, TiO 2 , CeO 2 , ZnO, CuO, SiO 2 and different quantum dots were shown to generate ROS and induce oxidative stress in different organisms [5, 10, 12, 2630]. Selected examples concerning ENM-induced oxidative stress or damage in microalgae, representative for aquatic phytoplankton are given in Table 1.
Fig.
…”
Section: Enms and Oxidative Stress In Aquatic Microorganismsmentioning
confidence: 99%